Head circumference percentiles in Indian children with Down syndrome - Kaur, Harvinder; Bhalla, Anil Kumar; Panigrahi, Inusha; Kaur, Rupinder; Sudhera, Neha (Frontiers in Pediatrics, 2025)
This study aimed to construct age- and sex-specific growth percentiles for head circumference (HC) that can be used as a reference for Indian children with Down syndrome (DS). Over 24 years, following a mixed-longitudinal growth research design, 2,327 head circumference measurements were performed on 1,125 (boys: 752, girls: 373) children with DS karyotypically proven as cases of free trisomy 21 who were aged <1 month to 10 years, following a standardized anthropometric technique. A steady increase in the mean head circumference of male and female children with DS was noted. Boys with DS had significantly larger HCs than girls. Our study showed that 12.9% of Down syndrome cases had normal head circumference, 27.2% had small heads, and the majority, 59.9%, had microcephaly. Head circumference percentiles for boys and girls with Down syndrome were constructed for ages <1 month to 10 years. There is a need to monitor the growth of children with Down syndrome using population-specific and specialized growth charts. The age- and sex-specific head circumference growth percentiles presented for Indian children with Down syndrome can be used for growth monitoring and inter-population comparison.